2002
DOI: 10.1215/s1522851701000059
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive molecular cytogenetic investigation of chromosomal abnormalities in human medulloblastoma cell lines and xenograft

Abstract: Cell lines and xenografts derived from medulloblastomas are useful tools to investigate the chromosomal changes in these tumors. Here we used G-banding, fluorescence in situ hybridization (FISH), spectral karyotyping (SKY), and comparative genomic hybridization to study 4 medulloblastoma cell lines and 1 xenograft. Cell line D-425 Med had a relatively simple karyotype, with a terminal deletion of 10q and amplification of MYC in double-minutes (dmins). FISH demonstrated that an apparent isochromosome (17q) by r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 0 publications
1
15
0
1
Order By: Relevance
“…Here, we identified many numerical and structural alterations in both cell lines evaluated, mainly chromosomal gain and structural rearrangement of chromosome 1 and 7. Likewise, cytogenetic studies performed in other MB cell lines and short-time cultures also have reported a high frequency of structural rearrangements on chromosomes 1, 7 and 17 (Bayani et al 2000;Aldosari et al 2002).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Here, we identified many numerical and structural alterations in both cell lines evaluated, mainly chromosomal gain and structural rearrangement of chromosome 1 and 7. Likewise, cytogenetic studies performed in other MB cell lines and short-time cultures also have reported a high frequency of structural rearrangements on chromosomes 1, 7 and 17 (Bayani et al 2000;Aldosari et al 2002).…”
Section: Discussionmentioning
confidence: 80%
“…Nowadays, cell lines represent an effective tool to study tumor biology, including cytogenetic and molecular heterogeneity, neoplasic behavior, biological pathways of tumor maintenance, chemo-and radiosensitivity, as well as testing new targeted therapies (Keles et al 1995;Aldosari et al 2002). However, there are relatively few pediatric MB cell lines reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Complex translocations involving several chromosomal partners were present, as were double minute chromosomes and unidentifiable marker chromosomes. The SKY studies conducted by our group 13 and others 5,52 have identified the frequent involvement of chromosomes 1, 2, 3, 7, 10, 13, 14, 17, 18, and 22 in simple and complex translocations, contributing to copy number changes in those chromosomes (Fig. 3).…”
Section: Tumors With Neuroblastic or Glioblastic Elements (Embryonal mentioning
confidence: 89%
“…The CGAP database describes 15 cases 1,22,50,69,71,147,165,175,196,202,203,228 of choroid plexus papilloma or carcinoma. The karyotypes are predominantly near-diploid, hypodiploid, or hypotriploid, and are characterized by whole chromosomal gains and losses; these include gains of chromosomes 5,6,7,8,9,12,15,18, and 20 and losses of chromosomes 1, 3, 10, 16, 17, 21, and 22. In two cases, 50,69 diploid karyotypes were characterized by structural changes, including translocations, deletions, inversions, and the presence of markers, which were present as subclones.…”
Section: Nonglial Tumorsmentioning
confidence: 99%
See 1 more Smart Citation